2021
DOI: 10.1021/acsanm.1c00401
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Modified Gold Nanoparticles for Enhancing Antimicrobial Activity and Thermal Stability of Enzymes

Abstract: The synthesis of nanoparticles using ionic liquids (ILs) has attracted intensive research; however, synthesis and surface tailoring of gold nanoparticles (AuNPs) using ILs for enzyme immobilization have not yet been reported. Herein, we synthesized the various IL-modified AuNPs using different ILs, which are having common cation 1-ethyl-3-methyl-imidazolium (EMIM) and variable anions [BF 4−1 (AuNP-IL1), (CH 3 OSO 3 ) −1 (AuNP-IL2), (CH 3 CH 2 OSO 3 ) −1 (AuNP-IL3), and Cl −1 (AuNP-IL4)] by reduction of gold sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…Lastly, the zeta potential result concludes that with the increase in the concentration of AuNPs, the surface charge of the Cyt- c -AuNPs systems change to positive values with higher values for higher concentrations of Cyt- c -AuNP-IL3. The results surmount the biocompatibility of IL-mediated AuNPs from the previous study 34 to next and advanced levels subsiding the effects of higher temperature and long-term preservation on the activity and stability of enzymes.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Lastly, the zeta potential result concludes that with the increase in the concentration of AuNPs, the surface charge of the Cyt- c -AuNPs systems change to positive values with higher values for higher concentrations of Cyt- c -AuNP-IL3. The results surmount the biocompatibility of IL-mediated AuNPs from the previous study 34 to next and advanced levels subsiding the effects of higher temperature and long-term preservation on the activity and stability of enzymes.…”
Section: Resultsmentioning
confidence: 63%
“…33 In the previous work, our group has synthesized AuNPs using 1-ethyl-3-methyl-imidazolium (EMIM)-based ILs with various anions such as tetrafluoroborate [BF 4 ] À1 for AuNP-IL1, methylsulfate [CH 3 OSO 3 ] À1 for AuNP-IL2, ethylsulfate [C 2 H 5 OSO 3 ] À for AuNP-IL3 and chloride [Cl] À1 for AuNP-IL4, and therefore, enhanced the immobilization of the lysozyme enzyme, in turn enhancing the activity at room temperature. 34 Although, in the previous study, a higher enhancement in the activity has been observed along with preferential binding by the Michaelis-Menten constant and specific constant, the effect of multiple stresses such as temperature and long-term preservation with time has not been witnessed. Therefore, in the current study, the activity and thermal stability of Cyt-c were enhanced competitively in the presence of IL-mediated AuNPs against temperature change up to 90 1C and long-time preservation for 45 days.…”
Section: Introductionmentioning
confidence: 74%
“…Additionally, the peak at 1409 cm −1 is assigned to the asymmetric and symmetric C–H scissoring vibrations of the CH 3 –N + moiety and clearly shows the presence of H-bonding between AuNPs and IL, which is in accordance with the reported literature. 30 The IL contributes to the π-electron density of the system enhancing the speed of electron transfer due to a smooth conductive pathway. The results of UV and Raman spectra confirm these interactions within the system.…”
Section: Resultsmentioning
confidence: 99%
“…8,[27][28][29][30][31] Our research group has been diligently studying the exposure of various protein structures to numerous co-solvents to get an outlook towards the stability of the biomolecules in these solvents. 1,[32][33][34][35][36][37][38] Recently, with the emergence of the neoteric solvents, DESs, we have investigated the protein friendly behaviour in these solvents. There are only a handful of reports available related to protein stability and refolding ability in DESs.…”
Section: Introductionmentioning
confidence: 99%